2014
DOI: 10.1002/clen.201300869
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Reductive Decomposition of Perflurooctanoic Acid in Water: Effect of Temperature and Ionic Strength

Abstract: Aqueous photo‐reductive decomposition of perflurooctanoic acid (PFOA) was investigated as a function of temperature (293, 298, and 313 K) and ionic strength (2.5, 5.0, or 20.0 mmol/L as NaCl). As an advanced reduction process, iodide was used under UV irradiation to produce highly reactive reducing reagent hydrated electrons. PFOA was reduced by hydrated electrons and short‐chain perfluorinated acid intermediates including perfluoroheptanoic acid, perfluorohexanoic acid, perfluoropentanoic acid, perfluorobutyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Raising the temperature from of the measured rate constants, the overall apparent activation energy (Ea) was calculated to be 4.74 kJ/mol. The Ea value is much lower than those obtained in the photoreductive decomposition of PFOA in UV/KI system (59.54 kJ/mol) [73] and in the PFOA pyrolysis (154±11 kJ/mol) [74]. The observed Ea is lower than the activatio n energies of the eaqreactions, which lie in the range of 6-30 kJ/mol [20].…”
Section: Temperaturementioning
confidence: 56%
“…Raising the temperature from of the measured rate constants, the overall apparent activation energy (Ea) was calculated to be 4.74 kJ/mol. The Ea value is much lower than those obtained in the photoreductive decomposition of PFOA in UV/KI system (59.54 kJ/mol) [73] and in the PFOA pyrolysis (154±11 kJ/mol) [74]. The observed Ea is lower than the activatio n energies of the eaqreactions, which lie in the range of 6-30 kJ/mol [20].…”
Section: Temperaturementioning
confidence: 56%
“…Based on the temperature dependence of the measured rate constants, the overall apparent activation energy (E a ) was calculated to be 62.86 kJ/mol. This value is slightly higher than that obtained in the photoreductive decomposition of PFOA with hydrated electrons (59.54 kJ/ mol) [61], but much lower than that of PFOA pyrolysis (154 ± 11 kJ/ mol) [62]. Kim and Carraway indicated that the activation energy could be lowered by ~ 40-60 kJ/mol in the presence of VB12 for the dichlorination of PCE [63].…”
Section: Effect Of Temperaturementioning
confidence: 61%
“… PFOA UV/KI Low-pressure Hg UV light (15 W; Wavelength = 254 nm; Photon flux = 9.9 × 10 −6 mol L −1 min −1 ) |PFOA| = 0.008 mg/L; |KI| = 0.60 mmol/L; Temperature = 293–313 K; Ionic strength = 2.5–20 mmol/L; pH = 9; Time = 6 h 100 47.7–80.9% 3.2 × 10 −1 – 1.5 h −1 Effect of temperature and ionic strength on the degradation of PFOA was studied. The efficiency showed positive correlation with both temperature and ionic strength [ 133 ] PFOS VUV VUV:Low pressure Hg lamp (10 W; wavelength = 254 nm and 185 nm) |PFOS| = 0.2 mg/L; | | = 0.60 mmol/L; pH = 10; Time = 4 h 46.2% 30% 1.2 × 10 −1 h −1 The effect of light source in UV/sulphite and VUV/sulphite process showed the VUV/sulphite showed higher degradation efficiency due to the increased amount of generated reactive species [ 134 ] UV/ 85.8% 64.6% 4.8 × 10 −1 h −1 VUV/ UV: low pressure Hg lamp (11W; wavelength: 254 nm) 97.3% 68.5% 8.7 × 10 −1 h −1 PFOS UV/NTA Low-pressure Hg UV light (14 W; Wavelength = 254 nm; Photon flux = 9.9 × 10 −6 mol L −1 min −1 ) |PFOS| = 0.005 mg/L; |NTA| = 2 mM; pH = 10; Time = 10 h 85.4% 46.8 2.7 × 10 −1 h −1 The UV/NTA process showed high efficiency as NTA not only act as photosensitizer to induce water photodissociation and photoionization but act as • OH scavenger, thus reducing its recombination with hydrated electron [ 135 ] PFOA Vis/IAA/HDTMA-Montmorillonite Low-pressure Hg UV light (36 W; Wavelength = 254 nm; Photon flux = 4.5 mW cm −2 ) |PFOA| = 10 mg/L; |IAA| = 1 mM; |clay mineral| = 2.2 g/L pH = 3; Time = 5 h 100% 90% (within 10 h of reaction) …”
Section: Advanced Reduction Processes For Pfas Degradationmentioning
confidence: 99%